2015
DOI: 10.1007/s10461-014-0974-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Age at HIV Diagnosis in Cohorts in the United States, the Caribbean, and Central and South America

Abstract: In the United States (USA), the age of those newly diagnosed with HIV is changing, particularly among men who have sex with men (MSM). A retrospective analysis included HIV-infected adults from 7 sites in the Caribbean, Central and South America network (CCASAnet) and the Vanderbilt Comprehensive Care Clinic (VCCC-Nashville, Tennessee, USA). We estimate the proportion of patients <25 years at HIV diagnosis by calendar year among the general population and MSM. 19,466 (CCASAnet) and 3,746 (VCCC) patients were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…A recent study in Mexico City found that the proportion of individuals entering care who were diagnosed with HIV before the age of 25 significantly decreased from 1995–2012, highlighting that even if younger individuals are diagnosed early they may be delaying their entry into care. [ 37 ] Results from our study are consistent with this observation, with older individuals entering care with very low CD4 cell counts. Although we were unable to assess whether late entry into care was due to delayed testing or delayed presentation to care, our findings highlight the importance of promoting testing among older individuals who may be considered lower risk by providers, and who may not perceive the extent of their risk for HIV.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study in Mexico City found that the proportion of individuals entering care who were diagnosed with HIV before the age of 25 significantly decreased from 1995–2012, highlighting that even if younger individuals are diagnosed early they may be delaying their entry into care. [ 37 ] Results from our study are consistent with this observation, with older individuals entering care with very low CD4 cell counts. Although we were unable to assess whether late entry into care was due to delayed testing or delayed presentation to care, our findings highlight the importance of promoting testing among older individuals who may be considered lower risk by providers, and who may not perceive the extent of their risk for HIV.…”
Section: Discussionsupporting
confidence: 89%
“…The trend towards younger age at diagnosis in both heterosexuals and MSM are also observed in the United States [ 36 , 37 ]. Similarly, the median age at HIV diagnosis among MSM also declined from 38.8 years in 2007 to 35.9 years in 2009 in Victoria, Australia.…”
Section: Discussionmentioning
confidence: 92%
“…Expanding the utility of clinical databases to include social determinants and to link maternal and pediatric databases are goals of our CCASAnet network, as well as improving the quality and completeness of data collection. 3637 …”
Section: Discussionmentioning
confidence: 99%